Case reports of two siblings with autism spectrum disorder and 15q13.3 deletions - Sawako Furukawa; Itaru Kushima; Branko Aleksic; Norio Ozaki (Wiley, 2023)
Abstract Background Copy number variations (CNVs) have been implicated in psychiatric and neurodevelopmental disorders. Especially, 15q13.3 deletions are strongly associated with autism spectrum disorder (ASD), intellectual disability (ID), schizophrenia (SCZ), attention deficithyperactivity disorder (ADHD), and mood disorder. Case Presentation We present two siblings with ASD. They had a father with bipolar disorder (BD). Patient 1 is a 21‐year‐old female with ASD and mild ID, who had language delay and repetitive behavior in childhood, social difficulties, and refused to go to school because of bullying. She was hospitalized in a psychiatric hospital several times. Patient 2 is a 19‐year‐old male with ASD and ADHD. He did not have developmental delay, but had social difficulties and impulsiveness, then refused to go to school because of bullying. He was treated by a psychiatrist for anxiety and disrupted sleep rhythms. Array comparative genomic hybridization was performed for the siblings and parents. 15q13.3 deletions were detected in the siblings and their healthy mothers. No other pathogenic CNVs were detected. We performed whole‐genome sequencing of the family and identified 13 rare missense variants in brain‐expressed genes, which may be responsible for the phenotypic differences between the siblings and their mother. Conclusions This study shows incomplete penetrance and variable expressivity in 15q13.3 deletions. We detected second‐hit variants that may explain the phenotypic differences within this family. In addition, detecting 15q13.3 deletions may lead to early diagnosis and a better prognosis with careful follow‐up.